Role of Nuclear Factor Erythroid 2-Related Factor 2 in Diabetic Nephropathy - Wenpeng Cui; Xu Min; Xiaohong Xu; Bing Du; Ping Luo (Journal of Diabetes Research)
Diabetic nephropathy (DN) is manifested as increased urinary protein level, decreased glomerular filtration rate, and final renal dysfunction. DN is the leading cause of end-stage renal disease worldwide and causes a huge societal healthcare burden. Since satisfied treatments are still limited, exploring new strategies for the treatment of this disease is urgently needed. Oxidative stress takes part in the initiation and development of DN. In addition, nuclear factor erythroid 2-related factor 2 (Nrf2) plays a key role in the cellular response to oxidative stress. Thus, activation of Nrf2 seems to be a new choice for the treatment of DN. In current review, we discussed and summarized the therapeutic effects of Nrf2 activation on DN from both basic and clinical studies.